Implementation of Embedded based Bank Security System using Knock-out Gas - S. Prasath, J.; Natesan, R.; Jeyakkannan, N. (International Journal of Engineering and Technology, 2018)
The number of banks and the number of theft increases rapidly in the recent years. Most of the customers are using bank operations for savings account, keeping valuable jewels in the bank locker and availing loan for purchase of home. Bank manager is responsible for customer’s documents such as varieties of deposits, jewels kept in locker etc. The conventional bank security system is not effective and theft of cash, jewels etc. happen easily. The police cannot find the robbers easily. This proposed bank security system is novel, highly secure and cost effective embedded system which ensures bank security by releasing knock-out gas. It is operated only during the closing hours of banks. When any robber tries to enter the bank, the sensor kept near the locker senses and sends the signal to the microcontroller. The microcontroller sends the signal to the relay circuit which activates the gas releasing equipment to release the knock-out gas for a specified period of time. The release of knock-out gas towards robber makes him fall down. The signal from the microcontroller also sends to the Bank higher official’s mobile through the GSM. The Bank security personnel can easily catch the robbers with the help of police. This proposed bank security system is fully automated system which ensures safety to highly valuable customer’s documents, cash, and expensive ornaments present in the bank locker.